The Impact of Adequate Selenium Intake on Severity Symptoms and Quality of Life among People with Allergic Rhinitis - Thanyapron Tiyawisutsri; Napassorn Suwanpanyakul; Weeraya Kongkasri; Kamonwan Thongsri; Roger Timothy Callaghan; Alongkote Singhato (Journal of Nutrition and Food Security, 2025)
Background: Selenium (Se) deficiency leads to impairment of human immune function. Allergic Rhinitis (AR) is one of the most common immune-related diseases that affects the quality of life among patients. This study aims to investigate the effect of adequate Se intake on the severity of symptoms and quality of life among participants with AR. Methods: A total of 60 participants were recruited for the study and were divided into 2 groups; adequate Se intake (adSe) group and inadequate Se intake (InadSe) group based on nutritional suggestion calculated using a nutritional software package. All the participants were asked to complete the self-reported validated questionnaire on the severity of their symptoms and quality of life impairment for patients with AR. Results: The participants in InadSe group obtained significantly higher scores in almost all the aspects of the severity of symptoms and quality of life impairment compared with participants in adSe group (P<0.05). In addition, the amount of daily Se intake of the participants in this study was negatively correlated with the total scores of the questionnaires (P<0.05).Conclusions: The findings of this study indicated adequate Se intake, according to the recognized dietary guidelines, which tends to reduce the severity of symptoms and improve the quality of life among people with AR.